The high renaissance [videorecording] - Dunlop, Geoff (Art of the Western world / executive producer, Perry Miller Adato, 1989)
Covers key aspects of high renaissance, including the advent of the artist as genius (Leonardo, Michelangelo, and Raphael), the rise of Rome as a center of artistic vitality, and venetian preoccupation with the quality of light (Giorgione and Titian). Also examines the social turbulence of the late sixteenth century and the reinterpretation of classical architectural principles.